How to Teach Adults : Plan Your Class, Teach Your Students, Change the World - Spalding, Dan (Jossey-Bass higher and adult education series., 2014)
"Your hands-on guide to teaching adults. no matter what the subjectIn this expanded edition of How to Teach Adults, Dan Spalding offers practical teaching and classroom management suggestions that are designed for anyone who works with adult learners, particularly new faculty, adjuncts, those in community colleges, ESL teachers, and graduate students. This reader-friendly resource covers all phases of the teaching process from planning what to teach, to managing a classroom, to growing as a professional in the field. How to Teach Adults can guide new instructors who are trying to get up to speed on their own or can help teacher trainers cover what their students need to know before they get in front of a class. It is filled with down-to-earth tips and checklists on such topics as connecting with adult students, facilitating discussions, and writing tests, plus everything you need to remember to put into your syllabus and how to choose the right textbook. Dan Spalding reveals what it takes to teach all students the skills they need to learn, no matter what the topic or subject matter. Full of vivid examples from real-world classrooms, this edition: Shows how to get started and tips for designing your course Includes information for creating a solid lesson plan Gives suggestions for developing your teacher persona How to Teach Adults offers the framework, ideas, and tools needed to conduct your class or workshop with confidence"--